Effects of an Integrated Rehabilitation Program on Fatigue in Patients with Pulmonary Tuberculosis - Nguantad, Sunisa; Puwarawuttipanit, Wimolrat; Lekdamrongkul, Pichitra; Rongrungruang, Yong (Siriraj Medical Journal, 2023)
Objective: This study aimed to assess the effect of a 6-weeks integrated rehabilitation program on fatigue in pulmonary tuberculosis patients. Materials and Methods: Sixty-eight participants were diagnosed with pulmonary tuberculosis receiving antituberculosis drugs treated for 2 weeks or more. Participants were randomly into experimental and control groups with 34 participants each. The experimental group received usual care with an integrated rehabilitation program. The control group received the usual care with given the option to engage in activities to reduce their own fatigue. Fatigue symptoms were assessed with PFS-12 at baseline, at week 3 and week 6 and using the Repeated measure ANOVA for statistical analysis. Results: The study found that the experimental group had a lower mean fatigue score at week 3 than at the pretest. At week 6, the mean fatigue score decreased significantly compared that at the pretest and compared to the control group with statistical significance (F = 9.698, p <.001), while no statistically significant differences were found in the control group (F = 1.687, p = .200) Conclusions: The integrated rehabilitation program statistically and significantly reduced the levels of fatigue in pulmonary tuberculosis in 3-6 weeks. Registration number: This study was registered at the Thai Clinical Trials Registry (TCTR20221202001). Keywords: Pulmonary tuberculosis; Integrated program; Fatigue; Line application